ANALISIS IMPLEMENTASI KURIKULUM MERDEKA DENGAN MODEL PJBL MATERI NILAI NILAI PANCASILA - Maharani, Dina; Ansori, Isa (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The purpose of this study is to describe the implementation of Merdeka Curriculum withthe PjBL model on Pancasila values material for grade IV students, as well as identifyobstacles and impacts. The method used is descriptive qualitative method with data collection techniques through observation, interviews, questionnaires, and documentation. Data analysis was carried out using the Miles and Huberman model, which included data collection, data simplification, data presentation, and conclusion drawing. The results of this study show that the implementation of Merdeka Curriculum at SDNPudakpayung 01 Semarang has gone well, although there are still obstacles, such as thelack of cooperation of students in groups and the difficulty of teachers in conductingindividual assessments during group work. The positive impact found is the increasedenthusiasm of students in project-based interactive learning, which encourages them tobetter understand and internalize the values and symbols of Pancasila.